Eco-Plastics in the Sea: Succession of Micro- and Macro-Fouling on a Biodegradable Polymer Augmented With Oyster Shell - Audrézet, François; Pochon, Xavier; Floerl, Oliver; Le Guen, Marie-Joo; Trochel, Branwen; Gambarini, Victor; Lear, Gavin; Zaiko, Anastasija (Frontiers in Marine Science, 2022)
Impacts of Marine Plastic Debris (MPD) on marine ecosystems are among the most critical environmental concerns of the past three decades. Virgin plastic is often cheaper to manufacture than recycled plastics, increasing rates of plastic released into the environment and thereby impacting ecosystem health and functioning. Along with other environmental effects, MPD can serve as a vector for marine hitchhikers, facilitating unwanted organisms’ transport and subsequent spread. Consequently, there is a growing demand for more eco-friendly replacements of conventional plastic polymers, ideally with fit-for-purpose properties and a well-understood life cycle. We enriched polybutylene succinate (PBS) with three different concentrations of oyster shell to investigate the dynamics of biofouling formation over 18 weeks at the Nelson Marina, Aotearoa/New Zealand. Our study focused on oyster shell concentration as a determinant of fouling assemblages over time. While generally considered as a waste in the aquaculture sector, we used oyster shells as a variable of interest to investigate their potential for both, environmental and economic benefits. Using bacterial 16S and eukaryotic 18S rRNA gene metabarcoding, our results revealed that following immersion in seawater, time played a more critical role than substrate type in driving biofouling community structures over the study period. In total, 33 putative non-indigenous species (NIS) and 41 bacterial families with putative plastic-degrading capability were detected on the different substrates. Our analysis of NIS recruitment revealed a lower contribution of NIS on shell-enriched substrates than unadulterated polymers samples. In contrast, the different concentrations of oyster shells did not affect the specific recruitment of bacterial degraders. Taken together, our results suggest that bio-based polymers and composites with increased potential for biodegradability, recyclability, and aptitude for the selective recruitment of marine invertebrates might offer a sustainable alternative to conventional polymers, assisting to mitigate the numerous impacts associated with MPD.